Up in Smoke? A Preliminary Open-Label Trial of Nicotine Replacement Therapy and Cognitive Behavioral Motivational Enhancement for Smoking Cessation Among Youth in Los Angeles. (6th December 2013) - Swanson, Aimee-Noelle; Shoptaw, Steven; Heinzerling, Keith Gregory; Wade, Adam C.; Worley, Matthew; McCracken, James; Wilson, Sarah A.; Asarnow, Joan; London, Edythe D.
<x xml:space="preserve">Abstract</x> In 2008–2009, we conducted a 6-week, open-label trial of transdermal nicotine replacement therapy and practical counseling for 34 adolescents seeking smoking cessation in Los Angeles. Dependent outcomes were study retention, use of the patch, and 7-day quit status at the end-of-study and at follow-up visits. Predictors of outcomes included cigarette dependence, withdrawal symptoms, demographic and psychiatric measures, and other substance use. Variables significant in bivariate analysis (p < .10) were retained in a multivariate model. Subjects had significant pre-to-post reductions in quit rates, dependence, and withdrawal symptoms. Subjects also reported a high number of comorbidities. Implications for clinicians are discussed.